2023
DOI: 10.1007/s00787-023-02275-9
|View full text |Cite
|
Sign up to set email alerts
|

Is there sufficient evidence for the association between executive dysfunction and academic performance in adolescents with major depressive disorder?: a systematic review

Abstract: Adult depression, undoubtedly associated with executive dysfunction, leads to poor work performance. As depression in adolescents may have a negative impact on school performance, we aimed to analyse the possible relationship between selected executive deficits and academic performance. Executive dysfunctions may have more severe consequences on school performance at high school, as this stage of education requires engagement in long-term goals, whether writing an essay or preparing for an exam. Whilst inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…For instance, Smith et al (2023) conducted a study with 302 adolescent participants and found that teenagers with attention deficit or hyperactivity disorders generally exhibit lower levels of learning motivation, which in turn affects their academic performance. The internal factors such as sleep (Boraita et al, 2023;Chan et al, 2023;Hamvai et al, 2023), depression (Song et al, 2023;Urbanska-Grosz et al, 2023), and disordered social media use (Almarzouki et al, 2022;Sserunkuuma et al, 2023) also exert varying degrees of influence on academic performance. In this study, we primarily investigate the internal factors pertaining to learning state, encompassing self-efficacy and learning behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Smith et al (2023) conducted a study with 302 adolescent participants and found that teenagers with attention deficit or hyperactivity disorders generally exhibit lower levels of learning motivation, which in turn affects their academic performance. The internal factors such as sleep (Boraita et al, 2023;Chan et al, 2023;Hamvai et al, 2023), depression (Song et al, 2023;Urbanska-Grosz et al, 2023), and disordered social media use (Almarzouki et al, 2022;Sserunkuuma et al, 2023) also exert varying degrees of influence on academic performance. In this study, we primarily investigate the internal factors pertaining to learning state, encompassing self-efficacy and learning behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The role of neurocognitive functioning is pivotal in understanding the emergence of suicidal behaviour among young people affected by mood disorders [52]. Depressed teens often demonstrate lowered executive functioning [53][54][55][56][57]. Cognitive models of depression propose that challenges in regulating mood might stem exactly from difficulties in executive functions, particularly inhibition and flexibility [58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Smith et al (2023) conducted a study with 302 adolescent participants and found that teenagers with attention deficit or hyperactivity disorders generally exhibit lower levels of learning motivation, which in turn affects their academic performance. The internal factors such as sleep (Boraita et al, 2023;Hamvai et al, 2023), depression (Song et al, 2023;Urbanska-Grosz et al, 2023), and disordered social media use (Almarzouki et al, 2022;Sserunkuuma et al, 2023) also exert varying degrees of influence on academic performance. In this study, we primarily investigate the internal factors pertaining to learning state, encompassing self-efficacy and learning behavior.…”
Section: Introductionmentioning
confidence: 99%